Communiquer par gestes au bout du monde : La Pérouse à Sakhaline (Między Oryginałem a Przekładem, 2025)
COMMUNICATION WITH GESTURES AT THE END OF THE WORLD: LA PÉROUSE ON SAKHALINThe article aims to comment on the few cases of interlinguistic and intersemiotic communication that took place during La Pérouse’s circumnavigation (1785-1788), as described in his logbook Voyage de La Pérouse autour du monde (L.A. Milet-Mureau éd., Paris 1797, volume 3) and in its Polish translation. As one of the expedition’s aims was to describe the hydrography of the North Pacific Ocean and its cartography, the navigator wanted to know whether Sakhalin was an island and whether it was possible to round it from the western side. By questioning the natives, the members of the expedition received answers expressed in gestures that were sometimes difficult to interpret. In the Polish translation of the logbook (Podróż p. La Perouse na odkrycia nowych krajów w latach 1785- 1786-1787 i 1788, Kraków 1801-1803), to correctly render the fragments related to La Pérouse’s interviews with the natives, the translator would have had to carry out an intersemiotic translation in addition to the interlinguistic translation: read the French text, translate it mentally into images, and then describe these images in Polish. A study of the target text shows that he has not done it.